2010
DOI: 10.1021/ja1011614
|View full text |Cite
|
Sign up to set email alerts
|

PbTiO3 Nanofibers with Edge-Shared TiO6 Octahedra

Abstract: A new tetragonal phase of PbTiO(3) was discovered, in which each TiO(6) octahedron pair shares an edge and stacks over following pairs in an interlaced manner to form a one-dimensional (1D) columned structure along the c-axis. This new tetragonal phase of PbTiO(3) transforms into a normal perovskite phase in air at elevated temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 11 publications
1
31
0
3
Order By: Relevance
“…If the energy of the crystal-crystal interface is larger than the energy of two crystal-melt interfaces, VM will be present within a propagating crystal-crystal interface. Theoretical predictions are confirmed experimentally for the PT from recently synthesized metastable, tetragonal preperovskite (PP) 14,15 to cubic perovskite (CP) in PbTiO 3 nanofibers-an important ferroelectric material. Thus, surface melting and large reshaping of long nanofibers into cubes with rounded faces, edges, and corners due to hydrodynamic flow are recorded in situ using transmission electron microscopy (TEM) in the temperature range of 823-923 K. High-resolution TEM (HRTEM) on the quenched sample confirmed that all PP and perovskite phases are separated by highly disordered interphases, which is consistent with quenched VM.…”
mentioning
confidence: 80%
“…If the energy of the crystal-crystal interface is larger than the energy of two crystal-melt interfaces, VM will be present within a propagating crystal-crystal interface. Theoretical predictions are confirmed experimentally for the PT from recently synthesized metastable, tetragonal preperovskite (PP) 14,15 to cubic perovskite (CP) in PbTiO 3 nanofibers-an important ferroelectric material. Thus, surface melting and large reshaping of long nanofibers into cubes with rounded faces, edges, and corners due to hydrodynamic flow are recorded in situ using transmission electron microscopy (TEM) in the temperature range of 823-923 K. High-resolution TEM (HRTEM) on the quenched sample confirmed that all PP and perovskite phases are separated by highly disordered interphases, which is consistent with quenched VM.…”
mentioning
confidence: 80%
“…[21] In particular, it has been predicted that CO and NO catalysis could be favored on ultrathin Pt(100) films supported on ferroelectric PbTiO 3 . [22] Various methods have so far been applied to fabricate 0D and 1D ferroelectric nanomaterials, including templated methods, [23][24][25][26] sol-gel processing, [27,28] soft-chemistry routes, [29] solvothermal/hydrothermal reactions, [30,31] and electrospinning techniques. [32,33] Despite much effort, there is still an absence of a simple wet-chemistry method to prepare 2D single-crystal ferroelectric nanomaterials, such as nanoplates and nanodiscs.…”
mentioning
confidence: 99%
“…1c and d) were obtained by a hydrothermal and subsequent solid state phase transformation, and these nanobers were characterized to grow along [001] with {100} facets exposed. 25,29 Single-crystal PT nanoplates were formed hydrothermally via a self-template growth process, where {001} are dominantly exposed.…”
Section: Resultsmentioning
confidence: 99%
“…24,25,27 The as-obtained PT products were dispersed in deionized water in an ultrasonic bath for 30 min, respectively. The Pt/PT nanostructures were obtained by adding 0.05 M chloroplatinic acid (H 2 PtCl 6 $6H 2 O, aq) into the above mentioned solutions containing PT nanostructures.…”
Section: Experimental Details Preparationmentioning
confidence: 99%